Polyphenolic Antioxidants in Bilberry Stems and Leaves: A Non-Targeted Analysis by Two-Dimensional NMR Spectroscopy and Liquid Chromatography–High-Resolution Mass Spectrometry - Anna V. Faleva; Nikolay V. Ulyanovskii; Alexandra A. Onuchina; Dmitry S. Kosyakov (Antioxidants)
Compared with those of berries, the stems and leaves of the genus Vaccinium are important and underestimated sources of polyphenols with high antioxidant activity. In the course of this work, aqueous methanol extracts of the aerial parts of common bilberry (Vaccinium myrtillus L.) and bog bilberry (Vaccinium uliginosum L.) were studied to analyze the component compositions of their biologically active polyphenolic compounds. The aqueous methanol fractions of the stems and leaves of the studied samples contained 8.7 and 4.6% extractives, respectively, and were comparable in total polyphenol content, but presented significant differences in antioxidant activity. The identification of polyphenolic compounds was carried out via the following two-stage analytical procedure: (1) non-targeted screening of dominant structures via the 2D NMR method and (2) analysis of HPLC-HRMS data via the scanning of precursor ions for a specific ion. A total of 56 phenolic compounds were identified, including the glycosides quercetin, proanthocyanidins, and catechins, as well as various conjugates of caffeic and p-coumaric acids, including iridoids. Some of the latter, such as caffeoyl and p-coumaroyl hydroxydihydromonotropein, as well as a number of lignan glycosides, were described for the first time in V. uliginósum and V. myrtillus.